BETWEEN DOCTRINE AND REGULATION: LEGAL PLURALISM IN CONTEMPORARY SHARIAH ECONOMIC LAW - Nurul Huda; Faisal Razak; John Smith (Sharia Oikonomia Law Journal, 2026)
Contemporary Shariah economic law operates within a pluralistic legal landscape shaped by the interaction between classical jurisprudence and modern regulatory frameworks. The expansion of Islamic finance across diverse jurisdictions has intensified tensions between doctrinal authority and institutional regulation, producing varying interpretations and governance practices. This study aims to examine how legal pluralism is constructed and managed within contemporary Shariah economic law, with particular attention to the relationship between doctrinal reasoning and regulatory structures. A qualitative normative–juridical research design is employed through systematic analysis of 92 legal documents, including fatwas, national regulations, and international standards across multiple jurisdictions. Analytical matrices and thematic coding are used to identify patterns of legal interaction, institutional integration, and interpretive divergence. The findings reveal that legal pluralism is a structural characteristic of Islamic financial governance, where integrated systems enhance coherence while decentralized arrangements increase fragmentation. Hybrid governance models demonstrate greater effectiveness in balancing doctrinal diversity with regulatory consistency. The study concludes that legal pluralism should be understood as a dynamic and productive condition rather than a problem to be eliminated, requiring governance frameworks that facilitate coordination between competing authorities while preserving epistemological diversity.